Global food security: facts, issues, interventions and public policy implications - Hanjra, Munir A.; Ferede, Tadele; Blackwell, John; Jackson, Tamara M.; Abbas, Akhtar (2013)
The global food security situation and outlook remains delicately imbalanced amid surplus food production and the prevalence of hunger, due to the complex interplay of social, economic, and ecological factors that mediate food security outcomes at various human and institutional scales. A growing population and rising incomes with the resultant nutritional transition of millions more people entering into the middle class are some of the unprecedented challenges that mankind has never handled before. Food production outpaced food demand over the past 50 years due to expansion in crop area and irrigation, as well as supportive policy and institutional interventions that led to the fast and sustained growth in agricultural productivity and improved food security in many parts of the world. However, future predictions point to a slow-down in agricultural productivity and a food-gap mainly in areas across Africa and Asia which are having ongoing food security issues. The problem of food insecurity is expected to worsen due to, among others, rapid population growth and other emerging challenges such as climate change and rising demand for biofuels. Climate change poses complex challenges in terms of increased variability and risk for food producers and the energy and water sectors. The major existing and emerging challenges to global food security are discussed in this chapter, giving relevant examples from around the world. Strategic research priorities are outlined for a range of sectors that underpin global food security, including: agriculture, ecosystem services from agriculture, climate change, international trade, water management solutions, the water-energy-food security nexus, service delivery to smallholders and women farmers, and better governance models and regional priority setting. There is a need to look beyond agriculture and invest in affordable and suitable farm technologies if the problem of food insecurity is to be addressed in a sustainable manner. This requires both revisiting the current approach of agricultural intervention and reorienting the existing agricultural research institutions and policy framework. Proactive interventions and policies for tackling food security are discussed which include issues such as agriculture for development, ecosystem services from agriculture, and gender mainstreaming, to extend the focus on food security within and beyond the agriculture sector, by incorporating cross-cutting issues such as energy security, resource reuse and recovery, social protection programs, and involving civil society in food policy making processes by promoting food sovereignty.